How to Write In a Write-In When There is No Writing In Place. - Stackpole, John D. (Parliamentary Journal, 2012)
The article offers the author's insights on the use of key-pad systems during election. The author states that there are system descriptions of hand-held voting devices that must be addressed including display options, response time to poll, and possibility of system break down. He also mentions the conflict between the requirement of Robert's Rules of Order Newly Revised (RONR) that all ballot elections be write-in vote especially for un-nominated electoral candidates with the use of key-pad.